2010
DOI: 10.1039/c0pp00039f
|View full text |Cite
|
Sign up to set email alerts
|

Exciplex-like emission from a closely-spaced, orthogonally-sited anthracenyl-boron dipyrromethene (Bodipy) molecular dyad

Abstract: A molecular dyad, , has been prepared that incorporates a boron dipyrromethene (Bodipy) group functionalized at the meso position with an anthracenyl unit. Emission from the dyad contains contributions from both localized fluorescence from the Bodipy unit and exciplex-like emission associated with an intramolecular charge-transfer state. The peak position, intensity and lifetime of this exciplex emission are solvent dependent and the shift in the emission maximum shows a linear relationship to the solvent pola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…Benniston et al. reported that a dyad of BODIPY and anthracene exhibited an exciplex‐like emission assigned to the intramolecular CT state . They remarked that a CT emission was not observed for 1,3,5,7‐tetramethyl BODIPY due to the restricted rotation between the BODIPY and phenylene ring .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Benniston et al. reported that a dyad of BODIPY and anthracene exhibited an exciplex‐like emission assigned to the intramolecular CT state . They remarked that a CT emission was not observed for 1,3,5,7‐tetramethyl BODIPY due to the restricted rotation between the BODIPY and phenylene ring .…”
Section: Resultsmentioning
confidence: 99%
“…Benniston et al reported that ad yad of BODIPY and anthracene exhibited an exciplex-like emission assigned to the intramolecular CT state. [18] They remarked that aC Te mission was not observed for 1,3,5,7-tetramethyl BODIPYd ue to the restricted rotation between the BODIPY and phenylene ring. [19] Since both BODIPY-AP and BODIPY-MeAP can rotate around the phenylene ring to ac ertain extent,t he red emissions observed in toluene and 1,4-dioxane are assigned to at wisted intramolecular CT (TICT) state delocalized over the BODIPY and anthracene moieties.…”
Section: Intermolecular Ct Complex and Tict Formation Of Bodipy-meapmentioning
confidence: 99%
“…22) has the anthracene unit attached directly to the 5-position of the BODIPY. 56 Despite the lack of methyl groups on the BODIPY core, the anthracene unit adopts a near-orthogonal geometry with respect to the BODIPY plane. This was also observed in the 1,3,5,7-tetramethyl analogue of the same BODIPY.…”
Section: Through-bond Energy-transfer Cassettesmentioning
confidence: 99%
“…In comparison, the structure of 1, with unsubstituted BODIPY and anthracene moieties, exhibited the largest C8─C15 bond length (1.501 Å). 43 Two major forms of crystal packing were found for the BAD systems. The first is the head-to-head arrangement, as for 2 ( Figure S29).…”
Section: Elucidation Of the Dyad Solid State Structuresmentioning
confidence: 99%